p53 gene mutation: software and database. - Béroud, C (1998)
A large number of different mutations in the p53 tumor suppressor gene have been identified in all types of cancer. As of October, 1997, this database (http:// perso.curie.fr/tsoussi ) contained >7500 mutations. Such a substantial increase since our previous reports should enable epidemiological analyses which were not previously possible. In order to analyse these new data, the UMD software has been improved. A new Web version of the UMD software enables online analysis of the database. The present report describes various improvements since the last release of the database.